The glory of God - Morgan, Christopher W. (Theology in community, 2010)
Introduction / Christopher W. Morgan and Robert A. Peterson -- The glory of God, present and past / Stephen J. Nichols -- The glory of God in the Old Testament / Tremper Longman III -- The glory of God in the Synoptic Gospels, Acts, and General Epistles / Richard R. Melick, Jr. -- The glory of God in John's Gospel and Revelation / Andreas J. Kstenberger -- The glory of God in Paul's Epistles / Richard B. Gaffin, Jr. -- Toward a theology of the glory of God / Christopher W. Morgan -- A pastoral theology of the glory of God / Bryan Chapell -- A missional theology of the glory of God / J. Nelson Jennings